Production Of Protein Hydrolysates From Soy Okara By Rhizopus Oligosporus - Sulaiman, Ummi Syakina (Universiti Sains Malaysia, 2020)
The objective of this research project was to produce protein hydrolysate from soy okara by means of okara fermentation by Rhizopus oligosporus. The specifics objectives are to determine the proximate composition of fresh okara and to determine the effect of fermentation variables (percentage of inoculum and thickness of substrate) of okara by R. oligosporus on fungal growth and amino acid production. R. oligosporus obtained from tempe was directly used as inoculum for okara solid state fermentation.